2023
DOI: 10.3390/ijms24021687
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Functional Characterisation of the Rat Ventral Caudal Nerve in a Model of Axonal Peripheral Neuropathy

Abstract: Peripheral Neuropathies (PN) are common conditions whose treatment is still lacking in most cases. Animal models are crucial, but experimental procedures should be refined in some cases. We performed a detailed characterization of the ventral caudal nerve to contribute to a more effective assessment of axonal damage in future PN studies. PN was induced via weekly systemic injection of a neurotoxic drug (paclitaxel); we compared the control and PN-affected rats, performing serial neurophysiological evaluations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
3
2
0
Order By: Relevance
“…However, we observed a similar persistence of caudal nerve axonal neuropathy in both the young and adult treated animals at the end of the follow-up period with a slight deterioration over time in NCS as expected in such a relevant axonopathy. 19 We also found a more evident fiber loss in adult treated rats compared to young treated animals in both caudal and sciatic nerves, in agreement with previous studies describing a substantial decrease in the density of unmyelinated and myelinated fibers, particularly in the caudal nerve, with maturation. [20][21][22] When analyzing behavioral tests, we found a statistically significant development of mechanical allodynia in the young PTX-treated animals, and a lower mechanical threshold in the adult PTX-treatedanimals compared to controls.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, we observed a similar persistence of caudal nerve axonal neuropathy in both the young and adult treated animals at the end of the follow-up period with a slight deterioration over time in NCS as expected in such a relevant axonopathy. 19 We also found a more evident fiber loss in adult treated rats compared to young treated animals in both caudal and sciatic nerves, in agreement with previous studies describing a substantial decrease in the density of unmyelinated and myelinated fibers, particularly in the caudal nerve, with maturation. [20][21][22] When analyzing behavioral tests, we found a statistically significant development of mechanical allodynia in the young PTX-treated animals, and a lower mechanical threshold in the adult PTX-treatedanimals compared to controls.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, neurophysiological studies showed both caudal and digital nerve axonopathy in the adult PTX‐treated group compared with the young PTX‐treated animals, which presented only caudal nerve axonopathy. However, we observed a similar persistence of caudal nerve axonal neuropathy in both the young and adult treated animals at the end of the follow‐up period with a slight deterioration over time in NCS as expected in such a relevant axonopathy 19 …”
Section: Discussionsupporting
confidence: 80%
“…NCS (as shown in Figure 4) mirrored information gained via morphological observations of the caudal nerves. In both experiments a length‐dependent axonopathy was demonstrated, far severer in the PTX animals than in OHP animals, with a minor motor involvement only in the PTX cohort, as expected on the basis of literature data 2,5,28,34,37 …”
Section: Resultssupporting
confidence: 84%
“…Therefore, it is crucial to have robust preclinical models addressing pathogenetic mechanisms 15 . In this regard in vivo models are pivotal and it is mandatory to use translational methods to promptly transfer data from bench to bedside and vice versa; nerve conduction studies (NCS) are quite a relevant option since they can be similarly performed at a preclinical and clinical level in CIPN 1,3,6,9,17,26,27,34 . However, an even more refined option can lead to deeper investigations on axonal damage mechanisms: nerve excitability testing (NET).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation